1999
DOI: 10.1080/00365519950185940
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Dade Behring N Latex Cystatin C assay on the Dade Behring Nephelometer II System

Abstract: The Dade Behring N Latex Cystatin C assay, a particle-enhanced nephelometric immunoassay for measuring serum cystatin C, was evaluated on the Dade Behring Nephelometer II. The assay time was 6 min and the throughput was 75 samples per hour. The sample volume was 40 microL and the measuring range was 0.25-7.90 mg/L. Imprecision studies revealed within-run CVs < 1.8% and between-run CVs < 1.8% in the concentration range 0.87-4.63 mg/L. Recovery was 92.4-101.3%. Linearity studies showed excellent correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
173
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(174 citation statements)
references
References 4 publications
0
173
0
1
Order By: Relevance
“…These suggested that CysC was stable for 7 days at ambient temperature, for 1-2 months at -208C and for at least 6 months at -808C (18,23,24). In our personal experience, the length of stability at -808C can be extended to several years.…”
Section: Stability Of Cyscmentioning
confidence: 81%
“…These suggested that CysC was stable for 7 days at ambient temperature, for 1-2 months at -208C and for at least 6 months at -808C (18,23,24). In our personal experience, the length of stability at -808C can be extended to several years.…”
Section: Stability Of Cyscmentioning
confidence: 81%
“…27 No major interference with haemoglobin, bilirubin, triglycerides, and rheumatoid factors have been demonstrated using the assays. 17,25 Reference intervals are established and the same reference interval can probably be used in children older than 1 year and in adults independent of gender. 16,28 Furthermore, cystatin C is independent of muscle mass in contrast to creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…17 The method was a fully automated particle-enhanced nephelometric immunoassay (PENIA). The assay time was 6 min for cystatin C compared to 5 min for creatinine and the sample volume was 40 mL serum or plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research suggests that cystatin C measures have little variation because of storage time or freeze-thaw cycles (1,16,17). A review of potential applications of cystatin C in research and clinical decision-making has been published (18); standardization of cystatin C measurements-a common issue with any analyte that gains widespread usage-should be a priority.…”
Section: Resultsmentioning
confidence: 99%